Strategi Respon PT Pertamina pada Krisis Dugaan Oplosan Pertamax dalam Pemberitaan Kompas.com dan CNN Indonesia: Analisis Situational Crisis Communication Theory (SCCT) - Dewi Puspitawati; Riski Apriliani (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The crisis of the alleged Pertamax fuel fraud involving PT Pertamina (Persero) has become an issue that has received widespread attention because it has the potential to damage the company's reputation as a national energy provider. This study has the aim of conducting analysis on PT Pertamina's crisis communication response strategy as represented in online media reports. The study used the Situational Crisis Communication Theory (SCCT) approach with a quantitative content analysis method on 41 articles from Kompas.com and CNN Indonesia at the period February 25 to March 25, 2025. The results showed that the most dominant strategy was denial, followed by justification, apology, and ingratiation. The dominance of denial indicates the tendency of companies to deny involvement in crises in order to protect reputation, which is then reinforced by rational explanations. Meanwhile, apology and ingratiation are used as an effort to restore image and rebuild public trust. Furthermore, no significantly discrepancy was found among the two media in representing PT Pertamina's crisis response strategy. These findings show that the communication strategies used are still defensive and less varied, so they need to be evaluated to improve the effectiveness of crisis handling.